UV-Nanoimprint and Deep Reactive Ion Etching of High Efficiency Silicon Metalenses: High Throughput at Low Cost with Excellent Resolution and Repeatability - Christopher A. Dirdal; Karolina Milenko; Anand Summanwar; Firehun T. Dullo; Paul C. V. Thrane; Oana Rasoga; Andrei M. Avram; Adrian Dinescu; Angela M. Baracu (Nanomaterials, 2023)
As metasurfaces begin to find industrial applications there is a need to develop scalable and cost-effective fabrication techniques which offer sub-100 nm resolution while providing high throughput and large area patterning. Here we demonstrate the use of UV-Nanoimprint Lithography and Deep Reactive Ion Etching (Bosch and Cryogenic) towards this goal. Robust processes are described for the fabrication of silicon rectangular pillars of high pattern fidelity. To demonstrate the quality of the structures, metasurface lenses, which demonstrate diffraction limited focusing and close to theoretical efficiency for NIR wavelengths λ ∈ (1.3 μm, 1.6 μm), are fabricated. We demonstrate a process which removes the characteristic sidewall surface roughness of the Bosch process, allowing for smooth 90-degree vertical sidewalls. We also demonstrate that the optical performance of the metasurface lenses is not affected adversely in the case of Bosch sidewall surface roughness with 45 nm indentations (or scallops). Next steps of development are defined for achieving full wafer coverage.